PENGARUH DEBT EQUITY RATIO (DER), RETURN ON ASSET (ROA), CASH POSITION (CASH), ASSET GROWTH (GROWTH) TERHADAP DIVIDEN PAYOUT RATIO PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR FOOD AND BEVERAGE YANG TERDAFTAR DI BEI PERIODE 2014-2016 - Nisrina Oktavia Lestari (Faculty of Social and Political Science, 2019)
The purpose of this research is to examine the influence factors which influence the Dividend payout ratio (DPR) at the Manufacturing company food and beverage sub sector listed in Indonesia Stock Exchange from 2014-2016. The number of samples of 3 companies from 18 companies. From the analysis result indicate that the variable of DER, ROA, CASH, GROWT simultant influence to dividend payout ratio, but partially variable of DER and ROA have positive but not significant effect which company must strengthen cash position and ability to get profit enhanced in order company ability paying dividends and firms in distributing dividends depends on the firm's strong earnings, so companies should be able to predict the increase in profits earned by the company. Due to the stability of profits earned and the payment of a stable dividend will make investors more interested in investing funds for the company. CASH and GROWTH variables have a negative and insignificant relationship, which means that firms must be able to increase cash position, and assets growth Keywords :Dividend Payout Ratio (DPR), Cash Position (CASH), Return on Assets (ROA Debt to Equity Ratio (DER), Asset Growth (GROWTH)